Indicator of harmful cyanobacteria using an odor-binding protein-based biosensor for β-cyclocitral detection - Wang, Chunmiao; Chang, Xinying; Gu, Zhenao; Qian, Yaohan; Liu, Wanqing; Jia, Anqi; Yang, Zhugen; Yu, Jianwei; Yang, Min (Elsevier, 2026)
β-Cyclocitral, a compound that causes a hay/woody/tobacco-like odor, is closely associated with cyanobacterial cell density and can serve as a biomarker for cyanobacterial blooms. Biosensors utilizing odor-binding proteins (OBPs) have been developed for detecting chemicals exhibiting odors; however, their performance in environmental water samples has been rarely reported. In this study, an OBP-based electrochemical biosensor was developed for the detection of β-cyclocitral by immobilizing human OBP2a on a gold screen-printed electrode via nitrocellulose membrane. 1:5 mm2/μL nitrocellulose membrane/methanol mixture solution and 100 μg/mL OBP2a were selected as the optimal concentrations for OBP2a immobilization. The optimized sensor showed concentration-dependent characteristics in the range of 0.1–1000 μg/L. The performance of OBP2a-based biosensor was first comprehensively evaluated. Compared to 10 typical odorants in drinking water, the biosensor showed a relatively higher affinity for β-cyclocitral. The biosensor had a good detection accuracy and precision in real water samples, with recoveries of 119.86% and 115.31% in dechlorinated tap water and raw water samples, respectively. It maintains good stability when stored at −20 °C, with a current decline of 5.3% on the 6th day. These results demonstrate that OBP2a-based biosensors show promising potential for detecting β-cyclocitral, providing a useful tool for early warning of cyanobacterial blooms.
Keywords: 40 Engineering; Bioengineering; Prevention; 3 Good Health and Well Being; 4004 Chemical engineering; 4005 Civil engineering; 4011 Environmental engineering; Drinking water; Odor-causing compounds; Odor-binding proteins; Biosensors; Cyanobacterial bloom